The results of scientific cooperation of NSC KIPT and TJNAF (USA) - Glamazdin, A.V.; Gorbenko, V.G.; Levchuk, L.G.; Pomatsalyuk, R.I.; Sorokin, P.V. (Вопросы атомной науки и техники, 2001)
As a part of the spin-physics program at the Jefferson Laboratory (TJNAF), a Møller polarimeter has been developed to measure the polarization of electron beam of energies between 0.8 and 6.0 GeV. Since April 1998, regular measurements with the polarimeter are made. Kharkov scientists participated in 14 from 17 experiments, which were done in the Hall A. The most interesting published results are presented.